"Dinner's ready!" A qualitative exploration of the food domain across the lifecourse. (1st September 2015) - Hooper, Carolyn May; Ivory, Vivienne Chisholm; Fougere, Geoff
Highlights: Recalled childhood dinnertimes matter to adult engagement with the food domain. Adult food-mood can enhance or detract from health and wellbeing. Health-enhancing adult food-mood is associated with fond memories of childhood dinnertimes. Food is a bore and a chore for adults who resent their childhood dinnertimes. Abstract: The influence of the childhood food domain on adult food-related practices is only partially understood. Through an interpretive study using in-depth life-story interviewing and narrative analysis, we aimed to discover how preferences and perceptions relating to the food domain become embodied during childhood, and once embodied, how these influence practices in adulthood. We observed distinct 'food mood' pathways seemingly anchored in childhood memories about dinnertime. One pathway led to food philosophies participants perceived to be beneficial for their health and wellbeing, whilst another led to perceptions of food as a chore and bore they would rather ignore. Parental attitudes were very important to the food domain of childhood, as this is now recalled through life-story narratives. Our findings suggest a positive relationship with the food domain needs to be fostered during childhood for the long-term protection and promotion of health and wellbeing in adulthood.